ANALISIS PENDAYAGUNAAN ZAKAT PRODUKTIF TERHADAP PENGEMBANGAN USAHA MIKRO MUSTAHIK (STUDI ZAKAT CENTER LAZISMU GRESIK) - Maulidya, Chaterin; Fahrullah, A'rasy (Universitas Negeri Surabaya, 2021)
The distribution of zakat in the form of productive zakat has been widely applied by the Amil Zakat Agency and the Amil Zakat Institution. Lazismu Gresik Zakat Center as an Amil Zakat Institution provides capital assistance to mustahik from productive zakat in order to develop their micro-businesses. This study intends to analyze how the Zakat Center Lazismu Gresik has utilized it in developing mustahik's micro-businesses and to find out the differences between micro-business development before receiving and after receiving productive zakat assistance. In this research, the method used is descriptive qualitative research by conducting an in-depth interview. This study shows the results that the utilization of productive zakat has a major effect on the development of mustahik-owned micro-businesses.